ESTUDO DA ADIÇÃO DA LIGNINA KRAFT NAS PROPRIEDADES MECÂNICAS DOS BRIQUETES DE RESÍDUOS DA INDÚSTRIA MOVELEIRA - Adriana de Fátima Gomes Gouvêa; Ana Márcia Macedo Ladeira Carvalho; Cláudio Mudadu Silva; Angélica de Cássia Oliveira Carneiro; Paulo Fernando Trugilho; Fabiana Paiva de Freitas; Lumena Boroni Valadares; Claudia Marcia Gomes; Emerson Belarmino Costa (Ciência Florestal, 2017)
In order to improve global effectiveness of energy production, a strategy is the model of bio-refineries in which all the components of biomass are totally used to produce a range of products with aggregated value. The kraft lignin is one of the products originated in the process of cellulose production that can be used in making densified products. The objective of this work was to evaluate the behavior of the addition of extracted kraft lignin of black kraft liquor in briquette manufactures with furniture industry waste, in the form of shavings and panel particles in different proportions. The briquettes were produced in laboratory briquetting, using the temperatures of 60, 75 and 90 o C. The pressing and cooling time was 5 minutes and pressure 68,9 x 10 5 N.m -2 (1000 PSI). The briquette quality was evaluated through determining the mechanical properties. The kraft lignin in adequate proportions and temperature showed advantages in the increase of resistance and the durability of the briquettes. The kraft lignin presented advantages such as agglutinative in briquette productions from wood waste at a pressing temperature of 90 o C with addition of 20% of kraft lignin, and at pressing temperatures of 60 and 75 o C at a proportion of addition of 40 and 60% of kraft lignin to wood waste, respectively.